Anatomical vs Functional Preservation of Facial Nerve in a case of Petrous Apex Meningioma - Khan, Robert Ahmed; Rahman, Md Moshiur; Khan, SIM Khairun Nabi; Kuddus, Md Ruhul (Bangladesh Journal of Neurosurgery, 2021)
Abstract not available Bang. J Neurosurgery 2021; 10(2): 216-222